Factors of Listening Anxiety among the Second Language Learners of Grade 5 in Pakistan - Saba, Rifat; Noreen, Sumaira (International Journal of Psychosocial Rehabilitation, 2020)
In second language acquisition, affective factors such as anxiety are being foregrounded. The importance of listening to anxiety has led to many types of research and discussions from various perceptions. In the present era, it is the main hindrance to the acquisition of a second language. Its study can open up future vistas for young learners. Studies on listening anxiety in Pakistan are scant in number. Currently, some English medium schools have prescribed listening in their curriculum; still, it is not being taught and tested seriously and causes listening anxiety among students. The current research investigated students’ anxiety in English listening comprehension by using a quantitative method. Participants of this research were 100 students of grade 5 in two private schools in Pakistan. Kim (2000) developed a valid tool (FLLAS) Foreign Language Learning Survey as an instrument for data collection. A careful analysis of data findings showed that a high level of anxiety is faced by students due to inadequate listening practice, content knowledge and lack of input. The highlighted areas may have some implications and suggestions for further future teaching of second language listening comprehension to L2 students.